THE RELATIONSHIP BETWEEN ANEMIA KNOWLEDGE, COMPLIANCE WITH IRON SUPPLEMENT CONSUMPTION, PROTEIN AND TANNIN INTAKE WITH ANEMIA CONDITION IN ADOLESCENT GIRLS AT SMP NEGERI 19 BENGKULU IN 2023 - Yunita Yunita; Wahnil Dia Handayani; Desri Suryani; Kusdalinah Kusdalinah (Poltekkes Kemenkes Bengkulu, 2023)
Puberty is a period of change from childhood to adulthood, during which rapid growth occurs, including reproductive function, which influences developmental changes both physically, mentally, and in social roles, characterized by biological and psychological growth and development. This study aims to determine the relationship between knowledge of anemia, compliance with consuming iron supplement (IS), protein, and tannin intake with the incidence of anemia in adolescent girls at SMP Negeri 19 Bengkulu City in 2023. This research is a quantitative study. The research design is cross-sectional with a person correlation test analysis. This sample is 44 female teenagers in class 8 of SMP Negeri 19 Bengkulu City. Data collection techniques used observation sheets, knowledge was measured using a questionnaire, compliance with Iron supplement (IS) consumption was measured using a control card for taking blood tablets that had been previously validated, protein and tannin intake was calculated using a 24-hour recall form for 3x recall, and the incidence of anemia was measured using easy touch. This research was conducted on 21 February-20 March 2023. Data analysis uses the person correlation test. The results of this study show that there is no relationship between knowledge of anemia and the incidence of anemia (0.137), there is no relationship between adherence to consuming blood tablets and the incidence of anemia (0.210), between protein intake and the incidence of anemia (0.407), and between tannin and the incidence of anemia (0.297) in adolescent girls at SMP Negeri 19 Bengkulu City.